Desain Serat Kisi Bragg berlapis Grafin untuk sensor temperatur Tinggi - Dedi Irawan; Miftahul Farhani Isty; Azhar; Nur Islami; Khaikal Ramadhan (Jurnal Penelitian Pendidikan IPA, 2023)
This article reported design of FBG Sensor layered by 2D Graphene Material. In this research, the FBG was coated with single layer graphene material, then the outher FBG has been coated with Aluminium, Chromium Oxide, PMMA, and Silica. The finite element method was used to analyze the profile  of each coated-FBG with a thickness of 20 µm. Furthermore, the sensitivity of each designed coated-FBGs for the temperature measurement was calculated in the range of 25 oC – 300 oC. Design and analysis of coated FBG found that the FBG coated with graphene then layered by PMMA material has the highest sensitivity of 406.4 pm/℃. Although the sensitivity was 395.73pm/℃ for PMMA material. It was followed by Aluminium coating material which yields the sensitivity of 71.367pm/℃. The Silica and Chromium oxide yield the same sensitivity of 13.73pm/℃. Furthermore, the simulation results shows that the design of coated FBGs with a Gaussian apodization has the narrowest FWHM width of 1.3 nm. While the Tanh and Uniform apodization yield FWHM width of 3.724 nm and 3.732 nm respectively. Certainly, the best FBG design for high temperature sensor was proposed by FBGs coated by graphene and layered with PMMA material with Gaussian apodization